43 Effects of steroidal implants on feedlot growth performance, carcass characteristics, and serum and meat estradiol-17β concentrations of Holstein steers. (30th November 2020) - Carvalho, Pedro; Felix, Tara; Perry, George
Abstract: Objectives were to determine the effects of implants on growth performance, carcass characteristics, and estradiol-17β (E2 ) concentrations in the serum and longissimus muscle of Holstein steers fed a grain-based diet. Seventy Holstein steers (initial BW = 275 ± 6.4 kg) were assigned to treatments: (1) Implanted on d 0 with Component TE-IS with Tylan (Elanco Animal Health, Greenfield, IN) and on d 84 with Component TE-S with Tylan (Elanco Animal Health) of the experiment; or (2) not implanted (control). Implanted Holstein steers were heavier (P ≤ 0.01) than nonimplanted Holstein steers on d 84, at time of reimplant, and at the end of the experiment (d 186). Implanting Holstein steers increased (P < 0.01) average daily gain (ADG) and dry matter intake (DMI) without affecting (P = 31) gain-to-feed ratio (G:F) when compared to steers that were not implanted. Carcasses from implanted Holstein steers had greater (P < 0.01) hot carcass weights (HCW) and longissimus muscle (LM) area than carcasses from nonimplanted steers. Implanting did not affect (P ≥ 0.21) other carcass characteristics. There was an increase (P = 0.03) of 1.3 pg of E2 /g of muscle when LM from implanted Holstein steers was compared to LM from nonimplanted steers. There was an implant × day interaction (P < 0.01) in circulating serum E2 concentrations. Serum E2 concentrations remained relatively constant in nonimplanted Holstein steers. In implanted steers, serum E2 concentrations increased (P < 0.01) after each implant. Serum E2 peaked at 28 d after the first implant and then declined after d 56. Implanting Holstein steers fed grain-based diets increased ADG, HCW, and LM area due to increased circulating E2 concentrations. Implants did increase LM E2 concentrations; however, changes were minimal compared to E2 concentrations in other human foods and were not great enough to warrant concerns regarding meat consumption from implanted animals.